[123I]CLINDE SPECT as a neuroinflammation imaging approach in a rat model of stroke - Ohshima, Makiko; Moriguchi, Tetsuaki; Enmi, Jun-ichiro; Kawashima, Hidekazu; Koshino, Kazuhiro; Zeniya, Tsutomu; Tsuji, Masahiro; Iida, Hidehiro (Elsevier, 2025)
Poststroke neuroinflammation exacerbates disease progression. [11C]PK11195-positron emission tomography (PET) imaging has been used to visualize neuroinflammation; however, its short half-life of 20 min limits its clinical use. [123I]CLINDE has a longer half-life (13h); therefore, [123I]CLINDE-single-photon emission computed tomography (SPECT) imaging is potentially more practical than [11C]PK11195-PET imaging in clinical settings. The objectives of this study were to 1) validate neuroinflammation imaging using [123I]CLINDE and 2) investigate the mechanisms underlying stroke in association with neuroinflammation using multimodal techniques, including magnetic resonance imaging (MRI), gas-PET, and histological analysis, in a rat model of ischemic stroke, that is, permanent middle cerebral artery occlusion (pMCAo). At 6 days post-pMCAo, [123I]CLINDE-SPECT considerably corresponded to the immunohistochemical images stained with the CD68 antibody (a marker for microglia/microphages), comparable to the level observed in [11C]PK11195-PET images. In addition, the [123I]CLINDE-SPECT images corresponded well with autoradiography images. Rats with severe infarcts, as defined by MRI, exhibited marked neuroinflammation in the peri-infarct area and less neuroinflammation in the ischemic core, accompanied by a substantial reduction in the cerebral metabolic rate of oxygen (CMRO2) in 15O-gas-PET. Rats with moderate-to-mild infarcts exhibited neuroinflammation in the ischemic core, where CMRO2 levels were mildly reduced. This study demonstrates that [123I]CLINDE-SPECT imaging is suitable for neuroinflammation imaging and that the distribution of neuroinflammation varies depending on the severity of infarction.